Improvement in Ship Repair Works: Experience in Implementation of Production Friendly Drawing in Shipyard - Mazlan Yasin; Nor Hasni Osman (International Journal of Supply Chain Management, 2018)
This paper is about studied the conflicts within the Production Department where ship repair works are carried out without proper establishment and full utilization of Production Friendly Drawing (PFD) produced by the Engineering Department. In order to resolve this problem, the qualitative study method was conducted in the shipyard to propose the best solution to overcome this issue. Production need to utilize the PFD to ensure ship repair works perform in accordance with best engineering practice while designer in Engineering Department must ensure the production drawing produced is friendly enough and accurate. PFD as one of the conflict resolution is chosen to overcome this issue while qualitative as a method being deploying to engage the production and designer intervention to come out with more efficient and effective solution for this problem. There are two findings have been discussed and compared in which the conclusion of the result was very significant.